The Day of Atonement: its interpretations in early Jewish and Christian traditions - Hieke, Thomas; Nicklas, Tobias (Themes in biblical narrative: Jewish and Christian traditions 1388-3909, 2012)
Das Geschenk der Versöhnung : Leviticus 16 als Schlussstein der priesterlichen Kulttheologie / Bernd Janowski -- The formulary of Atonement (Lev 16:21) in penitential prayers of the Second Temple period / Richard J. Bautch -- 'Commit injustice and shed innocent blood' : motives behind the institution of the Day of Atonement in the book of Jubilees / Anke Dorman -- The Day of Atonement in the Dead Sea scrolls / William K. Gilders -- The Day of Atonement in the late Second Temple period : Sadducees' high priests, Pharisees' norms, and Qumranites' calendar(s) / Isaac Kalimi -- Yom Kippur in Josephus / Christopher T. Begg -- Yom Kippur in Mishnah Yoma / Günter Stemberger -- The Day of Atonement of the Samaritans / József Zsengellér -- Fasting with Jews, thinking with scapegoats : some remarks on Yom Kippur in early Judaism and Christianity, in particular 4Q541, Barnabas 7, Matthew 27 and Acts 27 / Daniel Stökl Ben Ezra -- Christ as Hilasterion (Rom 3:25) : Pauline theology on the Day of Atonement in the mirror of early Jewish thought / Markus Tiwald -- Blood, life, and atonement : reassessing Hebrews' christological appropriation of Yom Kippur / David M. Moffitt -- The inauguration of Yom Kippur according to the LXX and its cessation or perpetuation according to the book of Hebrews / Gabriella Gelardini -- 'Seder Yom ha-Kippurim kakh hu' : zur Entwicklung der synagogalen Liturgie des Versöhnungstages / Andreas Lehnardt